On the class S $$ \mathcal{S} $$ origin of spindle solutions - Pieter Bomans; Christopher Couzens (Journal of High Energy Physics)
Abstract We analyse the backreacted geometry corresponding to a stack of M5-branes wrapped on a spindle, with a view towards precision tests of the dual N $$ \mathcal{N} $$ = 1 superconformal field theory. We carefully study the singular loci of the uplifted geometry and show that these correspond to C 3/Z n conical singularities. Therefore, these solutions present one of the first explicit realisations of honest locally N $$ \mathcal{N} $$ = 1 preserving punctures in class S $$ \mathcal{S} $$ . Additionally we study the symmetries and anomalies of the dual field theory through anomaly inflow and compute a variety of holographic observables including dimensions of BPS operators. This work paves the way for advancements in the study and identification of the precise dual field theories.